Strategi Kolaboratif Mengelola Kinerja: Fokus pada Team Efficacy dan Iklim Kerja - Masduki Asbari; Eko Riwayadi; Lala Hucadinota Ainul Amri (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study examines the influence of team characteristics (such as team efficacy) and environmental factors (such as emotional intelligence climate) on engineering team performance based on social cognitive theory (SCT). Data were collected through 157 questionnaires from engineering employees of a manufacturing company in Indonesia using random sampling method. Data analysis was conducted using SEM method with SmartPLS 3.0 software. The proposed model shows that work team planning acts as a mediator between team efficacy, emotional intelligence climate, and team performance. The findings provide an in-depth understanding of the factors that influence team performance in the context of the manufacturing industry. The results suggest that work team planning plays an important role in improving team performance through the effects of team efficacy and emotional intelligence climate. The practical implication of this research is the importance of company management to pay attention to both antecedent factors of team performance, both in terms of personal (efficacy) and environmental (emotional intelligence climate) in an effort to improve engineering team performance in a sustainable manner.